Old and New Approaches in Rock Art: Using Animal Motifs to Identify Palaeohabitats - Korpershoek, Mirte; Reynolds, Sally C.; Budka, Marcin; Riris, Philip (Quaternary, 2024)
Humans are well known to have made paintings and engravings on rock surfaces, both geometric motifs with an unclear representation, and representative motifs that refer to their activities and aspects of their environment. This kind of art is widespread across time and space and has throughout history been subjected to various kinds of approaches. Typically, rock art research focuses on its role in the development of the hominin brain and the capability of abstract thinking, as well as on interpreting representative and non-representative motifs. Ethnography and cognitive research have often stressed that rock art is the result of ritual practises and the expression of a shamanic belief system. However, representative motifs may also shed light on a region’s ecological and human prehistory. Here, we give an overview of the general development of rock art study: we highlight the development of artistic behaviour in humans by discussing aesthetic preferences, and the creation of simple geometric motifs and eventually representative motifs, before describing the theories that developed from the earliest study of rock art. These have largely focused on classification and interpretation of the motifs, and often centred on Palaeolithic material from Europe. We then move on to discuss how ethnography among rock art creating communities often suggests important relationships between specific animals in both the realms of spiritual belief systems and within the local environment. Lastly, we highlight how rock art reflects the local penecontemporaneous environment when it comes to depictions of animals, plants, technologies, humans and their activities. We argue that animal depictions are a useful subject to study on a large scale, as it is the most widespread representative motif, and the most appropriate subject to study when the goal is to draw conclusions on environmental changes. Rock art can fill gaps in the local archaeological record and generate new questions of it, but also offer new insights into the history of local human–animal interaction: animal species depicted and/or referred to in rock art are likely to have been a selection of spiritually important animals and a comparison to known information on human interactions with local species may reveal patterns among which animals are selected for local rock art depictions and which are not. Interregional comparison can in turn shed light on whether humans in general tend to ascribe meaning to the same types of animals. We end the review with suggestions for future study, with a special role for computational methods, which are suitable for the analysis of large databases of visual imagery.